Is familicide a distinct subtype of mass murder? Evidence from a Swiss national cohort. (17th February 2020) - Frei, Andreas; Ilic, Andrea
Abstract: Background: Familicide is defined as the killing of a whole family and, numerically, a form of "mass murder" (more‐or‐less three simultaneous killings). Switzerland has a lower rate of homicide than most other countries but a comparatively high share of homicides within the family. Aim: The aim of this study is to describe a complete national sample of familicides and compare them with other types of mass murders in the country over the same period. Methods: All cases of three or more unlawful homicides in one event in Switzerland between 1972 and 2015 were identified from court records and socio‐demographic, criminological, and psychological variables were extracted. Given small numbers, we rely on narrative comparisons. Results: There were 20 familicides in the 43‐year study, with 82 victims between them as well as six felony‐associated mass murders accounting for 19 victims and nine public mass murders with 44 victims. Only one familicide was a woman; mean age was 39.5 years (range 19–57 years). Most were in employment. Only four had a prior psychiatric history. Nine had a history of violent or intrusive behaviour, but a prior criminal conviction was rare. In all but one case there was evidence of psychosocial stressors; eight men were facing separation from a spouse. Just over half used guns, but only three used army weapons. The main difference between the familicides and the other mass killers was the much higher rate of suicide among the familicides. Conclusions: Familicides in Switzerland appear to be rare suicidal acts, generally carried out by previously successful and apparently stable middle‐aged men with often an inconspicuous psychiatric history or criminal record, differing considerably from other groups of mass killers. Expert responses, like the recently established multidisciplinary "threat management boards" in Switzerland, should bear in mind that the likely competent men involved may be good at covering their intent even from themselves.